Association of ANKK1 polymorphism with antipsychotic‐induced hyperprolactinemia. (8th May 2020) - Fedorenko, Olga Yu.; Paderina, Diana Z.; Loonen, Anton J. M.; Pozhidaev, Ivan V.; Boiko, Anastasiia S.; Kornetova, Elena G.; Bokhan, Nikolay A.; Wilffert, Bob; Ivanova, Svetlana A.
Abstract: Objective: Schizophrenia is a severe highly heritable mental disorder. Genetic polymorphisms of dopaminergic pathways are related to pathogenesis of drug response. Hyperprolactinemia (HPRL), a common adverse effect of antipsychotics, is attributed to blockade of dopamine D2 receptors. Ankyrin Repeat and Kinase Domain containing 1 ( ANKK1 ) gene is closely related to Dopamine Receptor D2 type ( DRD2 ) gene functioning. We examined whether the functional polymorphism rs2734849 in the ANKK1 gene is associated with antipsychotic‐induced HPRL. Methods: We recruited 446 patients with schizophrenia from among the Russian population of the Siberian region. The polymorphism rs2734849 in the ANKK1 gene was genotyped with The MassARRAY® Analyzer 4 by Agena Bioscience™, using the kit SEQUENOM Consumables iPLEXGold 384. Genotype and allele frequencies were compared between groups of schizophrenia patients with and without HPRL using the χ 2 test. Results: A comparison between schizophrenia patients with and without HPRL revealed significantly higher frequency of the C allele of the polymorphic variant rs2734849 in the ANKK1 gene in patients with HPRL as compared to the patients without it (χ 2 = 3.70; p = .05; odds ratio [OR] = 1.30 [0.99–1.69]). Conclusion: The functional polymorphism rs2734849 in the ANKK1 gene was associated with HPRL in patients with schizophrenia.